Propionic Acid, Induced in Gut by an Inulin Diet, Suppresses Inflammation and Ameliorates Liver Ischemia and Reperfusion Injury in Mice - Kawasoe, Junya; Uchida, Yoichiro; Kawamoto, Hiroshi; Miyauchi, Tomoyuki; Watanabe, Takeshi; Saga, Kenichi; Tanaka, Kosuke; Ueda, Shugo; Terajima, Hiroaki; Taura, Kojiro; Hatano, Etsuro (Frontiers in Immunology, 2022)
Liver ischemia and reperfusion injury (IRI) is one of the obstacles in liver surgery such as liver resection and transplantation. In this study, we investigated the preventive effect on mouse liver IRI by feeding mice with inulin, which is a heterogeneous blend of indigestible fructose polymer. Mice were fed either a control ordinary diet (CD) or an inulin diet (ID) containing 5% inulin in the CD, for 14 days before the ischemia and reperfusion (IR) maneuver. IR induced-liver damages were significantly ameliorated in the ID group, compared with those in the CD group. Feeding mice with an ID, but not a CD, elevated levels of Bacteroidetes among gut microbiota, and especially increased Bacteroides acidifaciens in mouse feces, which resulted in significant elevation of short-chain fatty acids (SCFAs) in the portal vein of mice. Among SCFAs, propionic acid (PA) was most significantly increased. The microbial gene functions related to PA biosynthesis were much higher in the fecal microbiome of the ID group compared to the CD. However, the action of PA on liver IRI has not been yet clarified. Direct intraperitoneal administration of PA alone prior to the ischemia strongly suppressed liver cell damages as well as inflammatory responses caused by liver IR. Furthermore, PA suppressed the secretion of inflammatory cytokines from peritoneal macrophages stimulated in vitro through TLR-4 with high-mobility group box 1 protein (HMGB-1), known to be released from apoptotic liver cells during the IR insult. The present study shows that PA may play a key role in the inulin-induced amelioration of mouse liver IRI.